The Cohort Effect Approach to a Friction in Students-Life Beyond Religious and Mental Health for Anxiety Disorder at IAIN Langsa - Iqbal, Iqbal; Afna, Mauloeddin; Sari, Rita (Dinamika Ilmu: Jurnal Pendidikan, 2020)
The article scrutinized a friction stem in students, a false or a real of hope, struggle, and retentive in life when anxiety attacking the consciousness and bridging religious tradition and mental health status. Beyond reality to fantasy, within the inner perceptive, students construct artificial facts in the brain to stimulate action as a course of reactions. The artificial are related to a hope, an expectation, inviting a positive outcome to be believed as an alternative fact to subdue anxiety of fears, which come to overshadow students’ mental status. For inner students’ mental status, there is friction which pressing one to another for their artificial feeling either became the greatest power or worst nightmare affected to daily life and exposure both internally and externally reactions. A cohort effect approaches were applied to observe a longitudinal study for students’ behaviors in contemplating anxiety disorder affect that relied on religious and mental health for an individual sample. Student’s behaviors respect a particular characteristic as the aging process. The approaches aimed at physical features; body shape, decision making, level of aggressiveness, fears, and matting patterns. Thus, students’ frictions are traceable to foresee students’ mental health disorders as an umbrella from a diverse field in clinical psychology.